Analisis Faktor Yuridis Penyebab Terjadinya Kekerasan Dalam Rumah Tangga Di Wilayah Ponorogo - Riska Andi Fitriono; Lushiana Primasari; Cornella Fithria Khairunnisa (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Domestic violence is known to increase significantly from year to year. There are 4 forms of domestic violence, namely physical, psychological, sexual and economic violence. Of the several forms of domestic violence, there is physical and economic violence that often occurs in Indonesian households. This happens because of several juridical factors that influence the emergence of domestic violence, but there are 2 juridical factors that greatly influence the existence of domestic violence, namely cultural factors and economic factors. The aim of this research is to gain knowledge about the factors that cause domestic violence and how to resolve domestic violence using the concept of restorative justice. Apart from that, the main aim is to ensure that domestic violence cases in Indonesia do not increase. The research method used in this article is a library study approach because it collects data from books, journals, the internet, or other written literature as a basis for writing research.